GIS based Approach for Suitability Analysis of Residential Land Use - Karna, Bikash Kumar; Shrestha, Shobha; Koirala, Hriday Lal (Geographical Journal of Nepal, 2023)
Developing countries in particular are experiencing a tremendous rise in urbanization. Population growth and internal migration generated rapid urbanization and uncontrolled infrastructure construction in urban and semi urban area in Nepal. In general, local needs for infrastructure development, and construction of housing and apartments are typically used to select the most suitable site for residential use. Identification of the criterion is crucial to a suitability analysis based on local needs. Site suitability analysis is used for identification of the best location or site for residential area using geographic information system (GIS) based on multi-criteria evaluation (MCE). Majority of research work, spatial analytical hierarchy process (AHP) is a suitable tool and used in suitability analysis purpose. The criteria were determined through prior work and customized in the local situation interaction with land use planner as expert perspective and focus group discussions, and utilized in land suitability analysis. In this study, GIS-MCE-AHP models is applied as an effective approach of spatial decision making process and play efficient vital role for identifying the potential areas for residential use. In the suitability residential index map, suitable level of residential area is covered only 5% and 38% land covered with the moderate suitable for residential area in Sambhunath municipality. The suitable for residential area is mainly occurred along the major road network and surrounding to the existing settlement area. GIS conjunction with MCE and AHP is useful for conducting land suitability analysis and serving as planning tool for suitable residential site.